Engine performance improvements through turbocharger matching and turbine design. Issue 9 (20th June 2022) - Chen, Shaolin; Ma, Chaochen; Zhang, Hong; Xu, Cheng; Lei, Fen; Feng, Tao; Cao, Gang; Yang, Hanqin; Wei, Chongfan
Abstract: It is interesting to improve engine system performance with turbocharger technologies. In this study, a systematic simulation for engine and turbocharger matching to provide full utilization of the turbocharger potential and improve the engine performance without sacrificing the emission is developed. A velocity ratio concept was proposed to count the turbocharger performance impacts due to the diameter ratio of compressor and turbine wheels. A design of experiments was used to optimize the turbocharger and engine performance for different turbocharger factors. A better‐matched turbocharger was obtained. A multidisciplinary optimization method was used to design a mixed flow turbine wheel to reduce the turbine velocity ratio at peak efficiency and increase the overall turbocharger efficiency. Results showed that about 0.4% torque improvements and 1.2% reductions in the engine brake‐specific fuel consumption were obtained without making any other changes to the engine. This study demonstrated that systematic simulations for engine systems and considering turbocharger wheel diameter ratio effects could further improve the turbocharged engine system matching and the engine performance. Abstract : A design of experiments was used to optimize the turbocharger and engine performance for different turbocharger factors. An optimally matched turbocharger was obtained under the conditions of the current turbocharger technologies. The multidisciplinary optimization method was used to design a mixed flow turbine wheel to reduce the turbine velocity ratio at peak efficiency and increase the overall turbocharger efficiency. Results showed that about 0.4% torque improvements and 1.2% reductions in the engine brake‐specific fuel consumption were obtained without making any other changes to the engine.